Surface Effects and Contact Mechanics X 2011
DOI: 10.2495/secm110251
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of microstructure and properties in laser cladding of a Ni-Cr-B-Si hardfacing alloy

Abstract: Ni-Cr-B-Si coatings are used in many industrial applications in order to improve wear and/or corrosion properties. These coatings have traditionally been deposited by thermal spray techniques but the laser cladding process is also being increasingly employed to produce Ni-Cr-B-Si coatings with superior functional properties. In this research, the microstructural evolutions and the phase formations in the laser cladding of a Ni-Cr-B-Si alloy and their effects on the hardness of the clad layer are discussed. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
0
9
0
1
Order By: Relevance
“…31 A similar study reported that the floret-shaped particles are eutectics consisting of Cr 2 B and Ni. 15 It was also stated that three types of Cr-borides can be formed namely, Cr 2 B, CrB, and Cr 5 B 3 wherein the formation of CrB occurs directly from the melt, while Cr 5 B 3 may form by the peritectic reaction of CrB and the melt or directly from the melt. 15 Another work involving the TEM examination of precipitates reported the formation of Cr 7 C 3 carbide and borides namely, Cr 2 B and CrB besides Ni 3 Si silicide in c-Ni matrix.…”
Section: Fe-sem and Xrdmentioning
confidence: 99%
See 3 more Smart Citations
“…31 A similar study reported that the floret-shaped particles are eutectics consisting of Cr 2 B and Ni. 15 It was also stated that three types of Cr-borides can be formed namely, Cr 2 B, CrB, and Cr 5 B 3 wherein the formation of CrB occurs directly from the melt, while Cr 5 B 3 may form by the peritectic reaction of CrB and the melt or directly from the melt. 15 Another work involving the TEM examination of precipitates reported the formation of Cr 7 C 3 carbide and borides namely, Cr 2 B and CrB besides Ni 3 Si silicide in c-Ni matrix.…”
Section: Fe-sem and Xrdmentioning
confidence: 99%
“…15 It was also stated that three types of Cr-borides can be formed namely, Cr 2 B, CrB, and Cr 5 B 3 wherein the formation of CrB occurs directly from the melt, while Cr 5 B 3 may form by the peritectic reaction of CrB and the melt or directly from the melt. 15 Another work involving the TEM examination of precipitates reported the formation of Cr 7 C 3 carbide and borides namely, Cr 2 B and CrB besides Ni 3 Si silicide in c-Ni matrix. 18 Thus, these results show that variation in the laser power had a significant influence on the precipitation behavior of Colmonoy-5 clads keeping in view that all other process parameters were kept unchanged.…”
Section: Fe-sem and Xrdmentioning
confidence: 99%
See 2 more Smart Citations
“…Несмотря на повы-шенный интерес к таким покрытиям, многие вопро-сы, связанные с изучением их формирования, влияния структурно-фазовых изменений исходных материалов на физико-механические свойства покрытий, в том числе и сопротивление усталости системы «покрытие-основа», остаются нерешенными [5]. Проведенные исследования самофлюсующихся сплавов Ni-Cr-B-Si с высоким со-держанием Cr и B показали, что для них характерно формирование различных типов микроструктур, зави-сящих от скоростей охлаждения и температуры [6].…”
Section: анализ литературных данных и постановка проблемыunclassified